Efficiency and power in energy conversion and storage : basic physical concepts - Christen, Thomas, 1963- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
This textbook provides the fundamental theoretical concepts of how to describe and optimize devices for energy conversion and storage. Focusing on power-efficiency relations which are the main ingredient for optimization, relations will be derived and discussed for various prototype systems like batteries, electro-motors, heat engines, solar, photodiodes, piezo-electrics, wind turbines etc. In contrast to other books, all models will be constrained to the simplest basics, allowing non-experts and beginners to easily grasp the essentials--
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
OCLC-licensed vendor bibliographic record.
Keywords: Power resources; Energy conversion -- Mathematics; Energy storage -- Mathematics; Electric power-plants -- Efficiency; TECHNOLOGY & ENGINEERING / Mechanical